Seizures after epidural blood patch in a postpartum patient later diagnosed with hypertension and proteinuria: a diagnostic conundrum. Issue 1 (24th February 2022) - Prichard, A.; Appiah, S.; Kearsley, R.; Arnold, G.
Summary: Seizures are a rare, but documented, consequence of accidental dural puncture and epidural blood patch. They are also the cardinal feature of eclampsia. We present a postpartum patient who suffered a tonic‐clonic seizure within 1 hour of an epidural blood patch procedure for a suspected post‐dural puncture headache. Investigations also revealed hypertension, proteinuria and subdural collections. This case demonstrates the diagnostic dilemma associated with postpartum headache and late postpartum eclampsia. We illustrate the importance of a thorough clinical assessment of postpartum patients presenting with headache, highlighting the possibility of more than one underlying pathological cause. We also consider the role of epidural blood patch in both precipitating, and preventing, complications of accidental dural puncture.